PRECARIOUS SETTLEMENTS IN A REGIONAL METROPOLIS OF NORTHEAST BRAZIL: THE CASE OF THE FORTALEZA CITY, CEARÁ STATECITY, CEARÁ STATE - Queiroz de Lima, João Sérgio; Santos, Jader de Oliveira (Caminhos de Geografia, 2018)
Housing problems in the world have resulted in precarious settlements in urban territories. In Brazil, these settlements reached 30% of urban homes at the beginning of the 21st century. The objective of this article is to recognize the situation of the settlements in the city of Fortaleza, capital of the Ceará State-Brazil, from the identification, spatialization, classification of typologies and demographic characterization. An integrative method is used for the systematization of georeferenced data in the Geographic Information System (GIS) and thematic mapping. Were identified 838 precarious settlements in the city, composed of 29 tenements, 16 irregular allotments, 48 housing estates, 128 community housing projects and 617 shanty-towns, with 352,597 families, 243,180 dwellings and 964,562 inhabitants. They represent 34% of the properties, 39.34% of the population and 19.19% of the territory, in areas with poor infrastructure, services and urban equipment, inhabited by the lower income population. The study provides the analytical basis of vulnerability to environmental disasters and potentiates discussion of urban space issues.